Konstruksi Berita Kudeta AHY di Partai Demokrat pada Kompas.com, Jpnn.com dan Sindonews.com - Wahilda, Kintan Nurul; Sumadiria, Abdullah S. Haris; Cholidah, Lida Imelda (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2024)
This study aims to reveal the framing in constructing news by reviewing the way the media composes, tells, to events. The construction theory views that reality is created and formed. Framing was revealed using the Zhongdang Pan and M. Kosicki model framing analysis method which observed the syntactic, script, thematic and rhetorical structures. The results of research on kompas.com tend to be pro with the issue of AHY's coup by framing AHY's failure and cadres' complaints, while jpnn.com is against the issue of AHY's coup by criticizing Moeldoko's actions, while sindonews.com tends to be neutral because it frames the AHY coup related to the upcoming 2024 presidential election. As a result, framing arises because of the different interests of the media.